The Relation of Adversity Quotient with Managerial Skill on Young Entrepreneurs of CafÃƒÂ©s in Malang - syarafina, Sabila Okta (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2019)
Appearance and development of various new cafes in Malang led to increase competition in the culinary business. This competition was one of the challenges that must be faced by young entrepreneurs.Ã‚Â To face the challenges that arise, Entrepreneurs were expected to have adversity quotient, that was the extent to a person can face challenges and solve the problems they have. Planning and making these strategies were related to managerial skill of each entrepreneur, so if an entrepreneur has a high level of adversity quotient and good managerial skill, the possibility to survive in the culinary business competition will increase, and vice versa.Ã‚Â This study aims to determine the ability of entrepreneurs to deal with business problems, so that their ability can continue to be improved to maintain their business. This study uses a quantitative approach with descriptive correlational methods and uses a purposive sampling technique. The data were collected using adversity quotient instruments and managerial skill performance assessment. The collected data was analyzed using product moment analysis.Ã‚Â The subject of thisÃ‚Â studyÃ‚Â was young entrepreneurs in Malang. The results of this study indicate that young cafÃƒÂ© entrepreneurs in Malang who have high adversity quotient also have high managerialÃ‚Â skill.Ã‚Â So that it can be concluded that young entrepreneurs was able to face challenges and solve existing business problems.Ã‚Â Suggestions from this studyÃ‚Â were addressed toÃ‚Â young entrepreneurs to understand their ability to deal with business problems, so their abilities can be continuously improved.Ã‚Â One ofÃ‚Â theÃ‚Â ways to improve this capability was to take part in training provided by various related agencies.